2003
DOI: 10.1086/374733
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational Radiation from Gamma‐Ray Burst Progenitors

Abstract: We study gravitational radiation from various proposed gamma-ray burst (GRB) progenitor models, in particular compact mergers and massive stellar collapses. These models have in common a high angular rotation rate, and the final stage involves a rotating black hole and accretion disk system. We consider the inspiral, merger, and ringing phases, and for massive collapses, we consider the possible effects of asymmetric collapse and break up, as well as bar-mode instabilities in the disks. We evaluate the orders … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
164
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(166 citation statements)
references
References 42 publications
2
164
0
Order By: Relevance
“…For an initially static star v (0) = 0. 7 In a general analysis one could pick ε = α and use the full expression for a ext i in Eq. (3.2).…”
Section: B Second Order Eulerian Perturbation Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…For an initially static star v (0) = 0. 7 In a general analysis one could pick ε = α and use the full expression for a ext i in Eq. (3.2).…”
Section: B Second Order Eulerian Perturbation Theorymentioning
confidence: 99%
“…7-15 of [5]). The detection of GWs from NS/NS coalescences could yield information about the equation of state (EOS) of ultra-dense nuclear matter, and about short-duration gamma-ray bursts [6,7]. Accurate predictions of the GW signal will be important for these purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Fragmentation instabilities could be produced in the core or in the disc (Fryer et al, 2002;Kobayashi & Mészáros, 2003). Rapid rotation could also give rise to rotational instabilities in the protoneutron star remnant (Dimmelmeier et al, 2008;Corsi & Mészáros, 2009b;Piro & Ott, 2011;Piro & Thrane, 2012) A number of studies have suggested there exists a sub-population of LGRBs known as low-luminosity GRBs (ll GRBs).…”
Section: Long Gamma Ray Bursts As Multi-messenger Targets For Gwsmentioning
confidence: 99%
“…A large variety of possible GW emitting mechanisms within these systems have been proposed, with some models predicting GW spectra that would be observable from distances of a few Mpc with initial LIGO and Virgo (Fryer et al 2002;Kobayashi & Mészáros 2003a;Corsi & Mészáros 2009;Piro & Pfahl 2007;Korobkin et al 2011;Kiuchi et al 2011). The afterglows of LGRBs, like the afterglows of SGRBs, typically show power law fading with α = 1−1.5.…”
Section: Stellar Core Collapsementioning
confidence: 99%